Neuroprotective effects of Chrysophanol against inflammation in middle cerebral artery occlusion mice. (6th September 2016) - Zhao, Yongmei; Fang, Yalan; Li, Jincheng; Duan, Yunxia; Zhao, Haiping; Gao, Li; Luo, Yumin
Highlights: CHR offers long-term neuroprotection against ischemic brain injury in vivo. CHR markedly reduces levels of several pro-inflammatory cytokines. Anti-inflammation of CHR may represent one of the mechanisms for treatment of stroke. Abstract: Ischemia/reperfusion (I/R) involves a cascade of reactions which ultimately lead to neuronal apoptosis or death. Inflammation plays an important role in this cascade. Chrysophanol (CHR), a purified active constituent from rhubarb, possesses many biological activities including anti-inflammation. The present study investigated the long-term neuroprotective effects of CHR on focal ischemic brain injury and the potential mechanism. Mice were subjected to 45-min middle cerebral artery occlusion and received either vehicle or CHR at 0.1, 1 or 10 mg/kg for 14 days after reperfusion. Neurological function, survival rate, brain tissue loss, expression of pro-inflammatory factors tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and nuclear factor-kappa B p65 (NF-κB p65) were then assessed. The results showed that treatment with CHR led to improved survival rate and reduced brain tissue loss compared with vehicle-treated mice, accompanied by improved neurological assessment and motor function, which were sustained for 14 days after I/R. I/R-induced expression of TNF-α, IL-1β and NF-κB p65 in neurons was markedly reduced in CHR-treated mice. These results indicate that CHR markedly attenuates brain injury after focal I/R, which is attributed at least in part to its anti-inflammatory actions.